Avaliação da efetividade de um programa de ensino sobre educação sexual para acadêmicos de pedagogia - Andrade, Josiane Conceição de (2019)
Sex Education at school is a task that requires preparation, organization, scientific knowledge and use of methodologies. Sexuality is an intrinsic characteristic of the human being, since it is present from the earliest stages of its development. In addition, it relates to social and cultural issues and the types of education and information that individuals have access to during their lifetime. Based on these considerations, this research aimed to adapt a teaching program on sex education for pedagogical students and to evaluate its effectiveness in producing changes in participants' knowledge and attitudes. The teaching program was adapted from Moura (2018) originally formulated for teachers. The adaptation was based on a previous survey of the questions that the academics thought would have difficulty answering if they were asked by the children during their professional practice. Therefore, it was an applied, qualitative and descriptive study. A total of 68 students from the Pedagogy course participated in the research, from two higher education institutions in the city of Foz do Iguaçu - PR, one public and one private.The study was conducted in three stages: in the first, the participants responded to the problem situations instrument; in the second, there was a teaching program in sex education; and in the third, the participants responded again to the initial instrument and to the evaluation instrument of the program components. The teaching program was based on the following subjects: sexual act, pregnancy, gender and pleasure.The analysis of the data from the pre and post-program instruments was performed statistically, and the data obtained from the program component evaluation instrument were analyzed descriptively, presenting the overall evaluation average and an average per component. The results showed increased capacity and comfort after the program, but only in gender situations there was no significant change, since they already had high scores in the pretest. More than 90% of participants rated the program as satisfactory, indicating only that it should have more workload and be available at more opportunities.The results of this research showed that the insertion of the theme, already in the initial series of the undergraduate degree in Pedagogy, strengthens the possibility that future professionals will become more prepared for the discussion of subjects about sex education. The program proved effective, even adapted and implemented in a new context. From the results of this research, it is possible to state that the program format can be used as a methodological basis for training in various areas and themes.